Resveratrol alleviates inflammatory response and neuron apoptosis in rats with traumatic brain injury - JIAN Yu, DAI Ling-yun, WU Feng-xue (Jichu yixue yu linchuang, 2020)
Objective To explore effects of resveratrol (RV) on inflammatory response and neuron apoptosis in rats with traumatic brain injury (TBI). Methods The rats were divided into control group (control), model group (constructing TBI rat model by fluid-percussion method), low, medium and high-dose RV groups with 8 animals in each. The changes of spatial learning and memory ability, hippocampal neuronal morphology, neurocyte apoptosis, inflammatory factors level and the presence of apoptosis-related proteins in each group after trauma were observed. Results Compared with control group, motion trajectory and latency of searching safety island were significantly prolonged in TBI group, hippocampal neuron damage was significant, neuron apoptosis rate, expression of caspase-3, Notch1 and Hes1 were significantly increased, and Bcl-2/Bax level was significant decreased (P＜0.05).Compared with TBI group, RV could shorten rat motion trajectory with dose-dependence, latency of searching safety island, alleviateneuron damage in hippocampus, down-regulate neuron apoptosis rate, expression of caspase-3, Notch1 and Hes1, and up-regulate Bcl-2/Bax level. Conclusions RV can effectively alleviate neuron damage and inflammatory response of TBI rats, and inhibit neuron apoptosis, which may be related to the down-regulating of Notch and Hes1 expression.